ANALISIS KERENTANAN USAHA BANK PERKREDITAN RAKYAT DI NTB PERIODE 2012-2021 - I Nengah Arsana; I Wayan Nuada (LPSDI Bina Patria, 2023)
This study was to determine the internal factors that influence the vulnerability of rural banks (BPR) in West Nusa Tenggara. BPR vulnerability is measured using the modified Crisis and Default Index (C&D Index), while the data analysis method uses logit regression. The sample for this research is 18 rural banks in West Nusa Tenggara for the period 2012 to 2021. The results show that the vulnerability of BPRs in NTB has fluctuated, where in the 2012-2014 period the average BPR was identified as not vulnerable, the 2015-2017 period the average BPR was identified as vulnerable and in the 2018-2019 period the average BPR in NTB was again identified as not vulnerable, then in the 2020-2021 period BPR in NTB was again identified as vulnerable. Rural banks that are identified as vulnerable indicate that the BPR has experienced a decline in the intermediary function. Meanwhile, the variables that have a significant effect on the Crisis and Default Index are the assets utilization variable which has a negative effect which indicates that the higher the assets utilization ratio, the lower the vulnerability of rural banks in NTB and the cost of efficiency variable has a positive effect which indicates that the higher the cost of efficiency ratio, the increase the possibility of vulnerable BPR in NTB.